Slädhundarnas hemliga språk : beteenden observerade av slädhundsförare under ett långdistanslopp - Hällström, Marlene (SLU/Dept. of Animal Environment and Health (until 231231), 2022)
Sled dogs are covering hundreds of kilometers during a long-distance race. The sport has been questioned from an animal welfare perspective. Mandatory resting periods and regular veterinary checks are bound by rules, to assure animal welfare during long-distance races. Can the sled dogs’ welfare be further assured through observations and actions by mushers during the race stages? During Polardistans, the long-distance world championships 2022, 33 mushers were interviewed at two separate points. Eight behaviours related to possible welfare issues were identified from the interviews. The behaviours were compared to the veterinary clinical findings during the competition. The mushers had noticed behavioural changes in 26.8% of the dogs that showed clinical signs of pain during the veterinary check. The highest observational rate was of shoulder injuries where the mushers had predicted 40.0% of the clinical findings. This study shows that mushers can increase sled dog welfare through behavioural observations during long-distance stages. Further studies must be conducted to specify the significance of each behaviour and thereby guide the mushers to make the right decisions at the right time.